2008
DOI: 10.1002/dvdy.21610
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of primary cilia and Hedgehog signaling during development of the human pancreas and in human pancreatic duct cancer cell lines

Abstract: Hedgehog (Hh) signaling controls pancreatic development and homeostasis; aberrant Hh signaling is associated with several pancreatic diseases. Here we investigated the link between Hh signaling and primary cilia in the human developing pancreatic ducts and in cultures of human pancreatic duct adenocarcinoma cell lines, PANC-1 and CFPAC-1. We show that the onset of Hh signaling from human embryogenesis to fetal development is associated with accumulation of Hh signaling components Smo and Gli2 in duct primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 82 publications
(124 reference statements)
9
62
0
Order By: Relevance
“…Therefore, an interesting inquiry to be addressed in future studies is whether BBS patients and BBS protein-knockout mice normally express SSTR3 on the primary cilia of insulin cells. Cells of pancreatic ducts and islets possess the primary cilia, but acinar cells of the exocrine pancreas apparently lack them (1,5,22,39). An electron microscopic study by Yamamoto and Kataoka (39) has reported in detail the ultrastructure of primary cilia on islet cells of some animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an interesting inquiry to be addressed in future studies is whether BBS patients and BBS protein-knockout mice normally express SSTR3 on the primary cilia of insulin cells. Cells of pancreatic ducts and islets possess the primary cilia, but acinar cells of the exocrine pancreas apparently lack them (1,5,22,39). An electron microscopic study by Yamamoto and Kataoka (39) has reported in detail the ultrastructure of primary cilia on islet cells of some animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that EOC cells are mostly devoid of primary cilia, and we suggest that this in part may be due to increased expression of AURA in these cells. These findings are in agreement with other studies on cancer cells, such as pancreatic adenocarcinoma cells, basal cell carcinoma cells, and clear cell renal cell carcinomas that also have reduced frequency of primary cilia [44,46,83,84], which in some cases can be explained by over expression of AURA [83]. However, in contrast to, for example, pancreatic cancer Figure 7 Inhibition of Aurora A and effect on ciliary formation in cancer OSE cells.…”
Section: Discussionsupporting
confidence: 91%
“…cells that may not form cilia because the cells fail to enter growth arrest [84], cancer OSE cells, such as SK-OV3, enter growth arrest upon serum depletion at a level comparable to that of wt OSE cells. The vast majority of OVCAR3 cells also entered growth arrest upon serum depletion, although not as many as SK-OV3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In many tissues, aberrant activation or absence of ciliary signaling is correlated with uncontrolled cell division and cancer Kuehn et al, 2007;Mans et al, 2008;Michaud and Yoder, 2006;Nielsen et al, 2008;Plotnikova et al, 2008;Wong et al, 2009;Han et al, 2009). However, an immediate effect of ciliary removal, either of all adult primary cilia or specifically of cilia on neurons of the hypothalamus in adult mice, is hyperphagia (compulsive eating), which leads to obesity.…”
Section: Primary Cilia In Adult Tissuesmentioning
confidence: 99%